Tantangan Etika Penggunaan Artificial Intelligence dalam Pembelajaran Pendidikan Agama Islam: Perspektif Politik Pendidikan Islam di Era Transformasi Digital - Habib Fahrur Rozi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The advancement of artificial intelligence (AI) in education has significantly transformed the educational process, particularly in Islamic Religious Education (PAI). While AI facilitates the acquisition of information and the creation of educational materials, it also presents ethical issues such as dependence on technology, the spread of religious misinformation, and the possibility of academic plagiarism. The purpose of this scientific study is to investigate the political perspectives of Islamic education in the era of digital change as well as the ethical issues surrounding the use of AI in teaching Islamic Religious Education (PAI). This study employed a literature review strategy along with a qualitative approach. Information on the application of AI in Islamic education was gathered from various scientific publications, journal articles, and papers. According to the research findings, artificial intelligence (AI) has the potential to improve the teaching of Islamic Religious Education (PAI), but to remain in line with Islamic moral and spiritual principles, AI must be regulated and supervised. Thus, it is crucial to improve digital literacy and educational strategies that combine technology with student character development in the digital age.